1956
DOI: 10.3382/ps.0350372
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Immunity to Fowl Pox

Abstract: A BOUT twenty years ago, studies on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1956
1956
2003
2003

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…There were no deaths from pigeon-or fowl-pox vaccinations, nor were there any detectable adverse effects of multiple vac-I N A previous experiment (Seeger and Price, 1956), pigeon-and fowl-pox vaccines were administered to chicks at 1, 5, 10, and 15 days of age. It was found that pigeon-pox vaccine was only partially successful in developing resistance to later fowl-pox challenge, whereas fowl pox was highly successful.…”
mentioning
confidence: 98%
“…There were no deaths from pigeon-or fowl-pox vaccinations, nor were there any detectable adverse effects of multiple vac-I N A previous experiment (Seeger and Price, 1956), pigeon-and fowl-pox vaccines were administered to chicks at 1, 5, 10, and 15 days of age. It was found that pigeon-pox vaccine was only partially successful in developing resistance to later fowl-pox challenge, whereas fowl pox was highly successful.…”
mentioning
confidence: 98%
“…2,7 However, the results of those studies were inconclusive, and because the disease was considered largely a problem in older laying chickens, most recommendations called for the vaccination of pullets at 8-20 weeks of age. But frequent and disastrous outbreaks of FP in broiler chickens, particularly in the southeastern United States, prompted the development of new strategies, and by the 1950s, vaccination for FP in broiler chicks at 1 day of age was initiated.…”
mentioning
confidence: 99%
“…But frequent and disastrous outbreaks of FP in broiler chickens, particularly in the southeastern United States, prompted the development of new strategies, and by the 1950s, vaccination for FP in broiler chicks at 1 day of age was initiated. 7 In the 1970s, FP vaccine was combined with THV for inoculation at day-of-age. 5,8 Vaccines containing various combinations of live viruses, including THV, SB-1, FP virus, and IBD virus, are now used routinely for the vaccination of broiler chicks at the hatchery.…”
mentioning
confidence: 99%